Sociocultural and Demographic Factors That Impact on the Adoption of an Innovative Financial Service - Acuña Muñoz, Óscar Andrés (2020)
The objective of this study is to analyze the incidence of both sociocultural and demographic factors, which are involved in the decision-making process of individuals when adopting innovative financial services. To achieve the objective, the Theory of Planned Action and the Theory of Diffusion of Innovations are used as a basis. A questionnaire was applied as a measurement instrument in a population of 321 people with ages between 18 and over 60 years. The analysis of the collected data determines that factors such as the perception of utility are the ones that most directly influence people's decision-making to adopt innovative financial services, so it is necessary to emphasize the benefits of financial services to increase its level of adoption and thereby contribute to the development of the countries' financial systems.